Unraveling Potential Confounding Variables in the Association Between Maternal Malaria and Child Stunting in Papua: A Case-Control Study with Mantel-Haenszel Analysis - Felle, Zeth; Sahiddin, Muhamad (YCAB Publisher, 2024)
Background:Papua is a malaria-endemic region with Indonesia's highest annual parasite incidence. At the same time, stunting is a common child health problem in Papua. Malaria incidence in pregnant women is considered a risk factor for stunting in children. Thus, the identification of confounding factors in this relationship is necessary. Objective:The study aimed to determine significant confounding factors in maternal malaria and child stunting and clarify the true association between these two conditions. Methods: The study with a case-control design was conducted at 14 Puskesmas from May to September 2023. The sample size was 681 children, consisting of toddlers who were stunted and not stunted and were selected by probability sampling technique. Data collection used questionnaires and anthropometric measurements. Statistical analysis used Mantel-Haenszel chi-square with a cut-off point for changes in the estimated coefficient for determining confounding> 10%. Results: The results showed that the crude Odds Ratio of the effect of malaria incidence during pregnancy on the incidence of stunting in children was 1.746 (95% CI 1,062-2,872). Stratification analysis showed the adjusted Odds Ratio value of child sex (1.78), low birth weight (1.652), basic immunization status (1.771), breastfeeding status (1.753), maternal age (1.732), occupation (1.828), ethnicity (1.722) and family income (1.764). There were no potential confounding variables in the association between malaria incidence in pregnant women and childhood stunting (change in coefficient estimate <10%). Conclusions: Public health interventions aimed at preventing malaria during pregnancy can be used as a strategy to reduce the risk of childhood stunting. Keywords:Malaria; pregnancy; stunting; confounding; Indonesia